Butterfly Diversity in the Paddy Field Area of Paokmotong Village, Lombok Island - Mohammad Liwa Ilhamdi; Agil Al Idrus; Ovy Adelia Hidayat (BIOCHEPHY: Journal of Science Education, 2026)
Lombok Island harbours a rich butterfly fauna that plays a vital ecological role as pollinators and bioindicators of ecosystem health. This study investigated butterfly species diversity in the paddy field area of Paokmotong Village, East Lombok Regency, using an exploratory survey method across five observation zones: the northern, southern, eastern, and western field edges, and the central field transect. A total of 49 individuals belonging to eight species from three families (Pieridae, Hesperiidae, and Nymphalidae) were recorded. Eurema blanda and Leptosia nina (both Pieridae) were the most abundant species, while Nymphalidae exhibited the highest species richness with five species. The Shannon-Wiener diversity index (H') was calculated at 1.898, indicating moderate diversity. This value reflects a relatively stable habitat condition in terms of food availability, temperature, humidity, wind speed, and light intensity. The moderate diversity level suggests that, while the paddy field ecosystem of Paokmotong provides a reasonably supportive habitat for butterflies, environmental pressures such as pesticide use and low plant diversity may be limiting species richness. Conservation of wild flowering vegetation along field margins is recommended to sustain and enhance butterfly diversity in this agricultural landscape.